Effect of Emotional Intelligence on Adjustment Ability of 12 to 14 year old Students - Upadhyaya, Himani (International Journal of Advanced Research in Peace, Harmony and Education; Vol 7 No 1 (2022): International Journal of Advanced Research in Peace, Harmony and Education, 2022)
Main objective of the study was to study gender and area-wise effect of emotional intelligence on adjustment ability of 12 to 14 year old students. For achieving the objective the Investigator selected 300 students of 12 to 14 years of age, randomly (150 boys and 150 girls of urban and rural areas) of Jabalpur district. Emotional Intelligence Test of S. Mathur and Adolescent Adjustment Scale of Ragini Dube used for measuring Independent and Dependent variables of the present study. Data analyzed by ANOVA showed the main effect of Emotional Intelligence, Gender and Area at 0.01 level of significance, Interactional effect for Emotional Intelligence * Gender at. 0.05 and for Emotional Intelligence* Gender* Area at 0.01 level of significance. How to cite this article:  Upadhayaya H. Effect of Emotional Intelligence on Adjustment Ability of 12 to 14 year old Students. Int J Adv Res Peace Harm Edu 2022; 7(1): 7-10.